IMPLEMENTASI PASAL 59 AYAT (2) HURUF J UNDANG -UNDANG NOMOR 35 TAHUN 2014 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI KOTA BANJAR - Mamay Komariah (SUPREMASI HUKUM, 2021)
Child victims of sexual abuse who have traumatic impacts who serve child victims of violence that are so profound and difficult to cure. Psychological trauma to children who are victims of sexual crimes is difficult to remove from the child's memory, especially if the perpetrator is still and lives not far from the environment of the child, the victim who commits a crime in a crime. The importance of the victim's main concern in discussing crimes caused by the victim often has a very important role in the occurrence of a crime. The method used by compilers in this research is descriptive analysis, namely how to solve problems or answer problems that are tracing the road, classification, analysis, the data displayed with the aim of making a picture of an objective situation. Compilers also use a normative juridical approach, namely legal research that prioritizes researching library materials or what is called secondary data material. Implementation of Article 59 Paragraph (2) Letter J Law Number 35 Year 2014 Amendments to Law Number 23 Year 2002 Regarding Protection in the City of Banjar Has not been implemented optimally because it is still the infrastructure, budget and human resources who are experts in children specifically, therefore The government should add psychologists and psychiatrists to rehabilitate child victims of sexual abuse committed by the presence of the social service and the P2TP2A (Integrated Service Center for Women and Children) to carry out rehabilitation only to provide motivation and visits to families but still not maximally because one is functionally responsible for protection against child victims of sexual crimes crimes. It is hoped that the government can provide maximum rehabilitation for children who are victims of criminal acts because it is an obligation of the government. protection of the community and increasing human resources such as psychology and psychiatrists to provide rehabilitation services for child victims of abuse.